2007
DOI: 10.1038/sj.clpt.6100321
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of GMP Raw Materials for Use in Regenerative Medicine: hESC-based Therapies, Progress Toward Clinical Application

Abstract: The potential of somatic cell therapies from human embryonic stem cells (hESCs) as alternatives to traditional drug-based remedies for treating some of mankind's most debilitating diseases has resulted in the need to translate rapidly proof-of-principle and basic research into clinical application. Consequently, researchers and regulatory bodies are now facing one of the major obstacles of the field: the efficient and reproducible generation of clinical-grade cells suitable for producing therapeutic cell types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 16 publications
0
14
1
Order By: Relevance
“…Remarkably, approval from several regulatory agencies such as Human Fertility and Embryology Authority (HFEA), Human Tissue Authority (HTA) and Medicines and Healthcare products Regulatory Agency (MHRA) is essential for the derivation process of hESCs and their use in cell based therapies in UK (9). …”
mentioning
confidence: 99%
“…Remarkably, approval from several regulatory agencies such as Human Fertility and Embryology Authority (HFEA), Human Tissue Authority (HTA) and Medicines and Healthcare products Regulatory Agency (MHRA) is essential for the derivation process of hESCs and their use in cell based therapies in UK (9). …”
mentioning
confidence: 99%
“…The hESC can now be grown successfully on porous-membranes (Kim et al 2007) and on animal-free, human foreskin fibroblast feeder cultures (Meng et al 2008). Advances are being made in the use of xeno-free hESC culture components (McDevitt and Palecek 2008) and largescale culture under GMP guidelines (Hewitt et al 2007;McDevitt and Palecek 2008).…”
Section: Culture Conditionsmentioning
confidence: 98%
“…A roadmap for the systematic bioprocess production of stem cells has been extensively described (Kirouac and Zandstra 2008). Any genetic change or modification to a donor human cell, that is reprogrammed to become a pluripotent stem cell cultured ex vivo for a long period of time to generate tissue-specific lineages, would have to undergo many analyses (Maitra et al 2005;Hanson and Caisander 2005;Imreh et al 2006;Hewitt et al 2007). Two recent analyses of various hESC lines using whole-genome arrays showed that many of the cell lines exhibit an amplification of 2.5-4.6 Mb at 20q11.21, encompassing 23 genes in common, after long-term cell culture (Lefort et al 2008;Spits et al 2008).…”
Section: Culture Conditionsmentioning
confidence: 99%
“…Amit et al [23] first reported the successful use of knockout serum for ESC culture as a replacement for bovine serum, although this semi-defined serum replacement contains xenogenic or undefined substances such as bovine serum albumin [24]. Subsequently, a culture medium containing human-originated recombinant proteins was developed (X-VIVO 10 medium).…”
Section: Application Of 2d Niche Systems To Stem Cell Self-renewal Mamentioning
confidence: 99%